A study on implicature in English and Vietnamese funny stories. M.A. Thesis Linguistics: 60 22 15 - Nguyễn, Thị Hồng Nhung (ĐHNN, 2017)
This thesis was written in an attempt to uncover the implicature in English and Vietnamese funny stories in terms of maxims. The study is in three parts and the main part consists of three chapters. The first gives literature reviews on semantics, pragmatics and discourse issues, the second is about methodology and the last is findings and discussion.